Proyek Kontinum Publikasi Ilmiah Mahasiswa: Menggabungkan antara Kelas Reguler dan Kelas Pemantapan - Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to explain the combination of regular classes and consolidation classes into a continuum project in achieving student scientific publications. This research uses a qualitative approach by applying descriptive methods. The results and discussion of the research show that students' achievement of scientific publications has been taken through various serious steps, namely regular classes and consolidation classes, but it is necessary to combine the two into a continuum project. This research concludes that the continuum project as a combination of regular classes and consolidation classes is deemed necessary to increase the quality of students' scientific publications.